Ethiopian National Red Meat Development Strategy ( 2025-2031) - Berhie, Asmelash; Guangul, Solomon; Alemu, Tesfaye; Galmessa, Ulfina; Lema, Tesfaye; Asefa, Melake; Urga, Kebeki; Fufa, Leta; Getachew, Tesfaye; Belay, Berhanu; Tolera, Adugna; Yeheyis, Likawent; et al. (Ministry of Agriculture Ethiopia, 2025)
SummaryThe National Red Meat Development Strategy (2025-2031) provides a comprehensive framework to enhance Ethiopia's red meat sector, which is vital for supporting livelihoods and driving economic growth. Cattle, sheep, goats, and camels are essential sources of red meat; however, current production and productivity levels are significantly below their potential. Ethiopia’s average meat productivity and per capita consumption lag behind other Eastern African nations and the global average. This strategy aims to transform the red meat sector by improving production, productivity, and commercialization to meet the increasing demands of domestic and export markets. A thorough assessment of the current landscape identifies opportunities, challenges, and strategic issues that require prioritized interventions. Key strategies will include improving animal husbandry practices, implementing genetic improvement programs, establishing, and enhancing market linkages, and facilitating comprehensive value chain transformations. To effectively address these strategic issues, actionable points will include boosting red meat production by supporting smallholder finishing initiatives, developing commercial feedlots, improving rangeland productivity, nd optimizing ranching practices. Improving meat quality and reducing meat wastage are also critical priority, with initiatives aimed at raising standards and practices to ensure that red meat produced meets the necessary hygiene and handling standards for both domestic consumption and export markets. Selective breeding is identified as the primary approach for breed improvement, with crossbreeding being strategically employed in delineated and suitable areas. Community-based breeding approaches, successfully tested in small ruminants, are also considered as viable strategies. Strategically located collection centers will streamline product distribution and enhance market access. The strategy highlights strengthening producer cooperatives to foster collaboration and improve bargaining power among producers. Additionally, the strategy emphasizes the importance of animal identification, performance recording, traceability, and genetic evaluation as essential components for ensuring quality control, enhancing livestock management, and informing selection decisions.